PAPR Reduction in OFDM Systems (International Journal of Engineering and Computer Science, 2014)
Orthogonal Frequency Division Multiplexing (OFDM) is a multi-carrier transmission method which is most widely used in the field of communication. One of the major drawbacks of this system is Peak to Average Power Ratio (PAPR). There are various methods introduced for the reduction of PAPR in OFDM system. However these techniques have major drawback that they cause non-linear in-band distortion and out-of-band radiation, this reduces the system throughput. Thus, SHIFTING AND SWITCHING OF NULL SUB-CARRIERS, which is the proposed technique discussed in our report overcomes this problem. In this technique, we replace some of the transmitted data symbols by nulls, i.e. we introduce errors in the transmitted signal. At the receiver, an iterative decoder is used to correct the transmitter and channel errors.